Interferon-α and angiogenic dysregulation in pregnant lupus patients destined for preeclampsia (2015)
Objective. To investigate whether an elevatedinterferon-␣(IFN␣) level early in pregnancy is associ-ated with poor pregnancy outcomes and to examine the relationship of an elevated IFN␣level to angiogenicimbalance.Methods. Women were enrolled in a longitudinalcase–control study of pregnant patients with lupus.Serum samples obtained monthly throughout preg-nancy were assayed for IFN␣and for the antiangiogenicfactor soluble Flt-1 and the proangiogenic factor pla-centa growth factor (PlGF). Each of 28 patients withsystemic lupus erythematosus (SLE) with a poor preg-nancy outcome was matched to an SLE patient with anuncomplicated pregnancy and to a pregnant healthycontrol. The effects of IFN␣and/or soluble Flt-1 onhuman endothelial cells and endothelial cell–trophoblast interactions were assessed.Results. Compared to SLE patients with uncom-plicated pregnancies, patients with preeclampsia hadincreased IFN␣levels before clinical symptoms. Pa-tients without autoimmune disease who developed pre-eclampsia did not have increased IFN␣levels. In SLEpatients with low IFN␣levels, marked angiogenic im-balance (higher soluble Flt-1, lower PlGF, and highersoluble Flt-1:PlGF ratios) preceded maternal manifes-tations of preeclampsia, whereas in SLE patients withhigh IFN␣levels, preeclampsia occurred without evi-dence of systemic angiogenic imbalance. Treatment ofhuman endothelial cells with soluble Flt-1 inducedexpression of sFLT1 messenger RNA, and IFN␣dra-matically amplified responses to soluble Flt-1. In amodel of spiral artery transformation, only the combi-nation of IFN␣and soluble Flt-1 disrupted the ability oftrophoblast cells to remodel endothelial tube structures.Conclusion. Our findings identify a new mecha-nism by which IFN␣induces an antiangiogenic milieuand increases the sensitivity of endothelial cells tosoluble Flt-1, and suggest that elevated IFN␣levels maycontribute to the pathogenesis of preeclampsia in somepregnant patients with SLE